Sie sind auf Seite 1von 2

# 3.

Mathematical Induction
Solutions

## 1. Let P(n) be the proposition When n = 1,

‘ 1 × 4 + 2 × 5 + 3 × 6 +  n(n + 3) L.H.S. = 31 = 3
1 3(31 − 1)
= n(n + 1)(n + 5) ’. R.H.S. = =3
3 2
When n = 1 , ∴ L.H.S. = R.H.S.
L.H.S. = 1 × 4 ∴ P(1) is true.
=4
Assume that P(k) is true for some positive
1
R.H.S. = (1)(1 + 1)(1 + 5) integer k,
3 3(3k −1 )
=4 i.e. 3 + 32 + 33 +  + 3k = .
2
∴ L.H.S. = R.H.S. When n = k + 11
∴ P(1) is true. L.H.S. = 3 + 32 +  3k + 3k +1
Assume that P(k) is true for some positive 3(3k − 1)
= + 3k +1
integer k, 2
i.e. 1 × 4 + 2 × 5 +  k (k + 3) 3k +1 − 3 + 2(3k +1 )
=
1 2
= k (k + 1)(k + 5) .
3 3(3 ) − 3
k +1

=
When n = k + 1 , 2
L.H.S. = 1 × 4 + 2 × 5 +  + k(k + 3 ) + 3(3k +1 − 1)
=
(k + 1)(k + 1 + 3) 2
1 = R.H.S.
= k (k + 1)(k + 5) + (k + 1)(k + 4) P (k + 1) is true.
3 ∴
1
= (k + 1)[ k (k + 5) + 3(k + 4)] By the principle of mathematical induction,
3 P(n) is true for all positive integers n.
= (k + 1)[ k 2 + 8k + 12]
1
3 (b) 331 + 332 +  + 360
1
= (k + 1)(k + 2)(k + 6) = (31 + 32 +  + 360 ) − (31 + 32 +  + 330 )
3
3(360 − 1) 3(330 − 1)
1 = −
R.H.S. = (k + 1)[ (k + 1) + 1] [ (k + 1) + 5] (by (a))
2 2
3
1 3(3 − 3 )
60 30

= (k + 1)(k + 2)(k + 6) =
3 2
3 (3 − 1)
31 30

∴ L.H.S. = R.H.S. =
2
∴ P (k + 1) is true.
By the principle of mathematical induction, P(n) is 3. Let P(n) be the proposition ‘ 5n − 4n − 1 is
true for all positive integers n. divisible by 16’.
When n = 1,
2. (a) Let P(n) be the proposition 51 − 4(1) − 1 = 0 which is divisible by 16.
3(3n−1 )
‘ 3 + 32 + 32 +  + 3n = ’.
2 ∴ P(1) is true.

5
Assume that P(k) is true for some positive When n = 1 ,
integer k, L.H.S. = T1
i.e. 5k − 4k − 1 = 16 M where M is an integer. 2
=
When n = k + 1 , (1 + 2)(1 + 4)
5k +1 − 4(k + 1) − 1 = 5(5 k ) − 4(k + 1) − 1 2
=
= 5(16 M + 4k + 1) − 4(k + 1) − 1 15
7 2(1) + 7
= 80 M + 20k + 5 − 4k − 4 − 1 R.H.S. = −
12 (1 + 3)(1 + 4)
= 80 M + 16k
7 9
= 16(5M + k ) = −
12 20
∴ P(k + 1) is true.
2
=
By the principle of mathematical induction, P(n) is 15
true for all positive integers n. ∴ L.H.S. = R.H.S.
∴ P(1) is true.
4. Let P(n) be the proposition Assume that P(k) is true for some positive
‘ n 3 + 11n is divisible by 6’. integer k,
When n = 1 , 7 2k + 7
i.e. T1 + T2 +  + Tk = − .
13 + 11(1) = 12 which is divisible by 6. 12 (k + 3)(k + 4)
∴ P(1) is true. When n = k + 1 ,
Assume that P(k) is true for some positive L.H.S. = T1 + T2 +  + Tk + Tk +1
integer k, 7 2k + 7 2
= − +
i.e., k 3 + 11k = 6M where M is an integer. 12 (k + 3)(k + 4) (k + 3)(k + 5)
When n = k + 1 , 7 (2k + 7)(k + 5) − 2(k + 4)
= −
(k + 1) 3 + 11(k + 1) 12 (k + 3)(k + 4)(k + 5)
= k 3 + 3k 2 + 3k + 1 + 11k + 11 7 2k 2 + 17 k + 35 − 2k − 8
= −
= (k 3 + 11k ) + 3k 2 + 3k + 12 12 (k + 3))k + 4)(k + 5)
= 6 M + 3k (k + 1) + 12 7 2k 2 + 15k + 27
= −
= 6 M + 6 N + 12 12 (k + 3)(k + 4)(k + 5)
7 (k + 3)(2k + 9)
(Since k (k + 1) must be an even number, we let = −
k (k + 1) = 2 N where N is an integer.) 12 (k + 3)(k + 4)(k + 5)
7 2k + 9
= 6( M + N + 2) = −
12 (k + 4)(k + 5)
∴ P(k + 1) is true.
7 2(k + 1) + 7
By the principle of mathematical induction, P(n) is R.H.S. = −
12 [(k + 1) + 3][(k + 1) + 4]
true for all positive integers n.
7 2k + 9
= −
12 (k + 4)(k + 5)

## 5. Let P(n) be the proposition ∴ L.H.S. = R.H.S.

7 2n + 7 ∴ P(k + 1) is true.
‘ T1 + T2 +  + Tn = − ’.
12 (n + 3)(n + 4) By the principle of mathematical induction, P(n) is
true for all positive integers n.